Pengaruh Keterampilan Komunikasi Interpersonal terhadap Kesiapan Mengajar Mahasiswa Prodi Kependidikan Fakultas Pendidikan Ekonomi dan Bisnis Universitas Pendidikan Indonesia - Mahmudah, Aisyah Nurul; Safira, Anita; Febrianto, Abi Sopyan (Jurnal Pendidikan Manajemen Perkantoran, 2024)
Interpersonal communication is the process of exchanging information, including ideas, ideas, feelings, thoughts and views that can strengthen the relationship between one party and another. This skill is really needed by students as prospective teachers to interact and build relationships with students both in the learning process and in daily relationships with students. This research aims to analyze the influence of interpersonal communication on the teaching readiness of students in the Education Study Program, Faculty of Economics and Business Education, Universitas Pendidikan Indonesian, including the Office Management Education, Economic Education, Accounting Education, and Business Education Study Program. This research is quantitative research with data collection techniques using questionnaires. The sample in this study consisted of 77 students. The results of the research show that interpersonal communication skills influence the teaching readiness of students in the Education Study Program, Faculty of Economics and Business Education, Universitas Pendidikan Indonesian.